2016
DOI: 10.18632/oncotarget.12425
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of action of HER2 targeted immunotherapy is explained by inhibition of NRF2 function in ovarian cancer cells

Abstract: Nuclear erythroid related factor-2 (NRF2) is known to promote cancer therapeutic detoxification and crosstalk with growth promoting pathways. HER2 receptor tyrosine kinase is frequently overexpressed in cancers leading to uncontrolled receptor activation and signaling. A combination of HER2 targeting monoclonal antibodies shows greater anticancer efficacy than the single targeting antibodies, however, its mechanism of action is largely unclear. Here we report novel actions of anti-HER2 drugs, Trastuzumab and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 98 publications
4
27
0
Order By: Relevance
“…Moreover, pertuzumab can abrogate the inhibitory effect of HER2 on the degradation of HER3 [ 174 ]. A recent study showed that both trastuzumab and pertuzumab inhibit NRF2 function in ovarian cancers and the combination of the antibodies produces more potent effects than a single antibody alone [ 175 ]. In summary, while the data regarding the mode of action of pertuzumab is quite limited, the available data mostly support the role of pertuzumab in blocking the heterodimerization of HER2, which in turn blocks the activation of HER2- and HER3-mediated signal transduction pathways leading to cancer cell proliferation and survival.…”
Section: Mechanisms Underlying the Action Of Pertuzumabmentioning
confidence: 99%
“…Moreover, pertuzumab can abrogate the inhibitory effect of HER2 on the degradation of HER3 [ 174 ]. A recent study showed that both trastuzumab and pertuzumab inhibit NRF2 function in ovarian cancers and the combination of the antibodies produces more potent effects than a single antibody alone [ 175 ]. In summary, while the data regarding the mode of action of pertuzumab is quite limited, the available data mostly support the role of pertuzumab in blocking the heterodimerization of HER2, which in turn blocks the activation of HER2- and HER3-mediated signal transduction pathways leading to cancer cell proliferation and survival.…”
Section: Mechanisms Underlying the Action Of Pertuzumabmentioning
confidence: 99%
“…In turn, this suggests that Heme oxygenase inhibitors could represent a potential therapeutic strategy. Following the findings of the role of NRF2 in chemoresistance, researchers have focussed on identifying NRF2 inhibitors to modulate NRF2 to overcome chemoresistance [51,55,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] .…”
Section: Nrf2 Signalling Pathway and Regulationmentioning
confidence: 99%
“…In anticancer chemotherapy, NRF2 and NRF-dependent genes have been implicated in the cellular resistance to a wide range of anticancer agents (e.g., tamoxifen, Cisplatin, Oxaliplatin, Cisplatin, Doxorubicin, and Etoposide) and cancer types [18][19][20][21][22][23][24][25] . Likewise, the NRF2-centred system and signalling pathway is shown to modulate the action and effectiveness of certain receptor targeted therapies [26][27][28]224,231,232] and potentially promoting cancer resistance to such interventions as Trastuzumab, Pertuzumab, Erlotinib, Lapatinib, imatinib, Gefitinib, Afatinib and Osimertinib. In both anticancer chemotherapy and receptor target therapy, the inhibition of NRF2 and its function seemingly and contextually enhanced drug sensitisation of cancers and/or helped to overcome drug resistance.…”
Section: Role Of Nrf2 In the Mechanism Of Action And Effectiveness Ofmentioning
confidence: 99%
“…This was as described for the cloning of HER2/HER3 promoters [ 22 , 24 ]. Briefly, approximately 1.5 kb proximal promoter region of HER1 was isolated, cloned, and used in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the majority of such studies, the focus was on the regulation of NRF2 activity and its function by these kinases. While the interaction and complex formation of NRF2 with HER2 have been reported to enhance HER signalling [ 22 , 24 ], we recently demonstrated the transcriptional regulation of HER2 and HER3 by NRF2 [ 22 ]. Further, we demonstrated a relationship between NRF2 function, HER2/HER3 signalling, ROS generation, and the sensitisation of ovarian cancer cells to the killing effects of the targeted therapeutics, trastuzumab, pertuzumab, or their combination [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%